1999
DOI: 10.1212/wnl.53.8.1774
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and quality of life outcome after thalamic stimulation for essential tremor

Abstract: Unilateral thalamic DBS for ET is cognitively safe and associated with improvements in anxiety and quality of life in the near term and in the absence of operative complications. Patients were better able to carry out activities of daily living after surgery, and they reported improvement in several psychosocial domains of quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 37 publications
6
101
0
2
Order By: Relevance
“…This reversibility is not possible in ablative procedures like thalamotomy and MRgFUS. 34 It should also be noted that although DBS is reversible and nonablative, it is still invasive-and complications like hemorrhage, seizures, suboptimal electrode placement, and infection can occur.…”
Section: Discussionmentioning
confidence: 99%
“…This reversibility is not possible in ablative procedures like thalamotomy and MRgFUS. 34 It should also be noted that although DBS is reversible and nonablative, it is still invasive-and complications like hemorrhage, seizures, suboptimal electrode placement, and infection can occur.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,24,29,38 Huss et al demonstrated no difference in the change in reported QOL between bilateral Vim DBS and unilateral procedures, including DBS and MRgFUS thalamotomy. 22 A randomized controlled study of MRgFUS thalamotomy described significant reductions of 46% in QUEST scores from baseline to 3 months after ablation as compared with a 3% reduction in the sham group.…”
Section: Figmentioning
confidence: 99%
“…14,34,38,40 In patients with ET, it has been suggested that there are complex, widespread alterations of white mater fiber integrity in both motor and nonmotor networks. 25 Thus, theoretically, thalamic procedures can produce disruption in the neuroanatomical pathway connecting the prefrontal cortex and subcortical areas, resulting in frontal lobe dysfunction.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations